EU Foreign Policy and Global Security : Instrument contributing to Stability and Peace (IcSP) - Kurnikova, Vasilisa (2024)
The main goal of this work is to determine the degree of effectiveness of the EU’s activities aimed at resolving crisis situations in the world, to determine the degree of EU involvement in the prevention of global conflicts, peacebuilding and the activities of the Union in general. Preparedness for crises in various regions of the world. The work plans to study the principles and tools of the EU to counter and prevent global and trans-regional threats. The main tool under study in the work is The Instrument contributing to Stability and Peace (IcSP), which is at the present stage the most relevant and, according to preliminary estimates, the most effective option for the EU’s influence on stability and well-being in the world. The work pays special attention to the study, econometric analysis and quantitative assessment of the success of using IcSP in practice during the study period 2013-2021, designated by the research regulations based on the beginning of the use of the tool under study and its current relevance. The work examined the main difficulties that arise when implementing IcSP in various regions of the world, including with regard to the applicability of the tool based on the nature of ruling regimes, the readiness of government entities to reform ineffective principles of leadership, cultural and national characteristics, as well as the readiness of representatives of regions of the world to counteract crisis situations with the help of advanced financial support mechanisms. The statistics of financing of numerous projects of various directions implemented by the EU using the IcSP tool were studied, which made it possible to form an empirical basis for quantitative assessment and econometric analysis of the effectiveness of IcSP.